2014
DOI: 10.1097/iop.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-Point Abobotulinum Toxin A Upper Face Rejuvenation

Abstract: Eighteen-point ABO-BTA upper face rejuvenation had a low rate of AE in this series in which majority was bruise at the lateral canthal area. They were significantly more in the first years of experience, subjects younger than 40, and who had touch-up injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Complications associated with botulinum toxin injection at the upper face include blepharoptosis, persistence of eyebrow asymmetry post-touch-up, eyebrow ptosis, diplopia, dry eyes, and eyelid edema. 4 , 5 There is a rare and interesting phenomenon without adverse complications and discomfort. This phenomenon is thought to be related to the patient’s physiological structure.…”
Section: Discussionmentioning
confidence: 99%
“…Complications associated with botulinum toxin injection at the upper face include blepharoptosis, persistence of eyebrow asymmetry post-touch-up, eyebrow ptosis, diplopia, dry eyes, and eyelid edema. 4 , 5 There is a rare and interesting phenomenon without adverse complications and discomfort. This phenomenon is thought to be related to the patient’s physiological structure.…”
Section: Discussionmentioning
confidence: 99%
“…BTA may be used for eyebrow lifting by targeting both glabellar and crow's feet areas. [5] It mostly results in lateral eyebrow lift [ Figure 1]. Ahn et al [6] showed an average elevation in the central brow of 1 mm and of 4.8 mm in the lateral brow.…”
Section: Botulinum Toxin a (Bta) Injectionmentioning
confidence: 99%
“…The effect is temporary and lasts for three to six months. [5] Pain, asymmetries, bruising and ecchymosis, erythema and edema, headache, diplopia, focal facial paralysis, dry eye syndrome, blepharoptosis, exaggeration of wrinkles, and muscle weakness are some of the adverse effects that might be seen by BTA injection for the upper face. [5]…”
Section: Botulinum Toxin a (Bta) Injectionmentioning
confidence: 99%
“…Consequently, the use of BoNTA in cosmetics for the effacement of dynamic wrinkles is wide-spread (20). Aside from the removal of wrinkles, the use of BoNTA continues to increase in a number of applications for its face-lifting effects (21), anti-photoaging effects on the skin, scar reduction (22) and flap survival improvement (23). …”
Section: Introductionmentioning
confidence: 99%